2017
DOI: 10.1159/000479560
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Type 2 Diabetes Mellitus and Arterial Stiffness: A Prospective Analysis Based on the Maine-Syracuse Study

Abstract: Background: The aim of this study was to investigate prospective associations between type 2 diabetes mellitus status and the gold standard non-invasive method for ascertaining arterial stiffness, carotid femoral pulse wave velocity. Methods: The prospective analysis employed 508 community-dwelling participants (mean age 61 years, 60% women) from the Maine-Syracuse Longitudinal Study. Pulse wave velocity at wave 7 (2006-2010) was compared between those with type 2 diabetes mellitus at wave 6 (2001-2006) (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…In most, but not all, studies in non-CKD populations, diabetic patients appear to have higher levels of PWV and CIMT than non-diabetic individuals. [39][40][41] Although the absence of differences in our study could be related to low power for these secondary comparisons, it is possible that the presence of CKD, which is per se associated with increased burden of arteriosclerosis and atherosclerosis, 37 has attenuated the differ- This is the first study examining the effect of diabetes mellitus on capillary rarefaction in CKD patients, using a detailed protocol of video-capillaroscopy. Among the strengths of this study is the careful design, including blinded matching of diabetic and non-diabetic CKD patients resulting in absence of between-group differences for a large set of baseline characteristics.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 88%
“…In most, but not all, studies in non-CKD populations, diabetic patients appear to have higher levels of PWV and CIMT than non-diabetic individuals. [39][40][41] Although the absence of differences in our study could be related to low power for these secondary comparisons, it is possible that the presence of CKD, which is per se associated with increased burden of arteriosclerosis and atherosclerosis, 37 has attenuated the differ- This is the first study examining the effect of diabetes mellitus on capillary rarefaction in CKD patients, using a detailed protocol of video-capillaroscopy. Among the strengths of this study is the careful design, including blinded matching of diabetic and non-diabetic CKD patients resulting in absence of between-group differences for a large set of baseline characteristics.…”
Section: Carotid Intima-media Thicknessmentioning
confidence: 88%
“… 30 , 31 However, there is some evidence claiming an effect of glycemic control on arterial stiffness. 10 , 13 This discrepancy may be due to the differences in the duration and the level of glycemic control and other potential parameters such as obesity, hyperlipidemia, hypertension, and hyperinsulinemia. Particularly, insulin level, apart from hyperglycemia, has been found to affect arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…10 Elias et al also demonstrated a higher PWV in T2D patients and found that the risk of arterial stiffness was over nine times higher in uncontrolled T2D compared to non-diabetic patients. 13 On the other hand, Chang et al did not observe any differences in CAVI between controlled and uncontrolled diabetes patients, when HbA1c at 7.5 was used as a cut-off value. 14 Similarly, Tian et al found that age, not HbA1c levels, is an independent predictor for CAVI in T2D.…”
Section: Introductionmentioning
confidence: 93%
“…Previous evidence on the distinct effect of DM on central BP and arterial stiffness mainly derives from studies evaluating levels in office conditions and studies using ABPM are scarce. In as secondary analysis in 508 (52 with DM and 456 without DM) community‐dwelling participants from the Maine‐Syracuse Longitudinal Study, diabetics presented significantly higher office PWV (12.5 ± 0.36 vs. 10.4 ± 0.12 m/s), while the risk of PWV levels ≥ 12 m/s was 9‐fold higher for those with uncontrolled DM compared to non‐diabetics (OR 9.14, 95% CI 3.23‐25.9, P < .001) 30 . A post hoc analysis of the French cohort DESIR (Data from an Epidemiologic Study on the Insulin Resistance syndrome) study, which compared BP and arterial stiffness measured in office conditions between 126 diabetic and 203 non‐diabetic patients found higher PWV in patients with DM [13.9 (11.6‐16.4) vs. 11.5 (9.9‐13.0) m/s, P < .0001] but similar cSBP and cDBP levels compared to their non‐diabetic counterparts 31 .…”
Section: Discussionmentioning
confidence: 95%